Epicutaneous sensitization. what do we know? - G. A. Novik; M. V. Zhdanova; A. S. Demidova (Бюллетень сибирской медицины, 2022)
Background. According to the currently existing hypothesis, epicutaneous sensitization is one of the leading mechanisms in the development of food allergy.The aim of this review was to analyze immune mechanisms in epicutaneous sensitization and the role of skin barrier impairment.We performed a literature search using PubMed, UpToDate, Web of Science, and Scopus databases by the key words: epicutaneous sensitization, atopic dermatitis, skin barrier impairment, food allergy. Articles were to be in open access and present the most relevant information on the topic. Studies were selected by the largest sample size and the highest citation index. Once publications were identified, they were reviewed by all the authors to select the studies that specifically addressed the theme of the review. A total of 101 publications from 1998–2000 were included in the study.This review article discusses the data of experimental studies, sets out modern ideas about the hypothesis of a double exposure to an allergen, and presents research data proving the clinical significance of epicutaneous sensitization in relation to food allergy. Knowledge about the mechanisms of epicutaneous sensitization development is necessary to elaborate strategies for prevention of food allergy. One of the modern trends in prevention is the use of emollients, which are supposed to restore the skin response. However, studies on preventive intake of emollients do not present a similar viewpoint.There is not enough evidence for or against the mechanism of epicutaneous sensitization as an indispensable condition for the formation of food allergies. Further research in this area is required.